Accommodating Analytic Hierarchy Process (AHP) for Elective Courses Selection - Sangka, Khresna Bayu; Muchsini, Binti (IJIE (Indonesian Journal of Informatics Education), 2018)
The determination of elective courses for students is one of many things that require some complex considerations. This complexity is motivated by psychological and non-psychological factors of human beings such as: learning motivation, lecturer and previous learning experience. Many students found difficulties if they have to decide in a complex options in which has the identical option. Thus, they made their decisions based on just one perceived factors alone without taking into account other factors which have great importance as well. Analytic Hierarchy Process (AHP) is one method that can be used as an appropriate decision supporting tool to reduce the complexity of decision making process. AHP provides analysis in the form of selected course recommendations that have a weight of rankings to the level of importance of each preferred alternative. This study was a preliminary study subjected to construct the real consideration from students’ point of view. In which very important to create a hierarchical perspective order for decision making process in both sides, student and education provider which was on Accounting Education Department, Faculty of Teacher Training and Education, Universitas Sebelas Maret Surakarta.